(untitled) ("Temas Sociais" Journal, 2025)
In Portugal there is an increasing demand for child foster care placements, however there is a shortage of carers within a solidary nature. Carers receive compensation for their service and professionalization is not considered. In light of the lack of knowledge in this area, our aim is to provide insights into financial matters, focused on remuneration’s impact on motivation levels to foster, and the evaluation of fostering experiences in relation to expenses. Thematic analysis of interviews with foster carers and practitioners (n=13) was informed by the Grounded Theory. The findings indicated financial considerations influence the motivation of specific applicant groups, namely unemployed. The financial strain associated with the direct and indirect costs of fostering was outweighed by the benefits of providing a family environment for foster children. Given the economic constraints, adequate compensation could be a form of recognition. To increase foster carers’ recruitment and retention it was advocated reimbursement of healthcare costs. Finally, we discuss implications for policy and practice and how the legal framework has evolved to carers’ dignified remuneration, tax and employment status.